Functional foods and nutraceuticals - Aluko, Rotimi E. (New York Springer, 2012)
Contents: Nutrient components of foods (bioactive carbohydrates; bioactive lipids; bioactive peptides; bioactive polyphenols and corotenoids); Specific functional foods (soybean; fruits and vegetables; milk and milk products; fish; miscellaneous foods and food components)
Includes index
Keywords: Công nghệ thực phẩm